1994
DOI: 10.1111/j.1365-2648.1994.tb01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Marital status, social support, and loneliness in visually impaired elderly people

Abstract: The purpose of this study was to investigate relationships between marital status, social support, and loneliness in visually impaired elderly people. The sample was derived from a larger study designed to examine loneliness in low-vision adults (Foxall et al. 1992). Subjects were 87 visually impaired elderly people who were at least 65 years of age, had a visual acuity of 20/70 or less in the better eye, had been visually impaired for at least 1 year, and were not totally blind. Data were collected by intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 26 publications
2
34
1
4
Order By: Relevance
“…Studies among the visually impaired elderly have shown that duration of visual impairment (Evans, 1983), adaptation to vision loss (Verstraten et al, 2005), a lack of social support (Verstraten et al, 2005), a small supporting social network (Barron et al, 1994), activity loss (Evans, 1983), and personality characteristics (Foxall et al, 1992) are determinants of feelings of loneliness.…”
mentioning
confidence: 99%
“…Studies among the visually impaired elderly have shown that duration of visual impairment (Evans, 1983), adaptation to vision loss (Verstraten et al, 2005), a lack of social support (Verstraten et al, 2005), a small supporting social network (Barron et al, 1994), activity loss (Evans, 1983), and personality characteristics (Foxall et al, 1992) are determinants of feelings of loneliness.…”
mentioning
confidence: 99%
“…Yapılan bazı araştırmalarda (Barron, Foxall, Dollen, Jones, ve Kelly, 1994;Yılmaz ve Aslan, 2013) evli öğretmenlerin, eşleri öğretmen olmasa ve aynı okulda görev yapmasalar bile, bekâr olanlara göre daha az yalnızlık yaşadıklarını tespit etmiştir. Bu açıdan ele alındığında, bu araştırmanın konusu olan öğretmen ile evli olma ve aynı okulda görev yapma durumu göz önüne alındığında, bu durumun öğretmen eşlere olumlu yönde katkı yapacağı ve yalnızlık duygusu yaşamayacakları söylenebilir.…”
Section: Sonuç Tartışma Ve öNerilerunclassified
“…Eşlerin aynı iş ortamında çalışmalarına dair yapılan araştırmalar incelendiğinde, genel olarak girişimci çiftler (Barron, Foxall, Dollen, Jones ve Kelly, 1994;Dahl, Praag ve Thompson 2014;Dyer, Dyer ve Gardner, 2012;Lee, 2005;Marshack, 1993;Parker, 2005), aile şirketleri (Fitzgerald ve Muske, 2002;Peksaygılı ve Tutan, 2015) üzerinde yoğunlaştığı görülmektedir. Fitzgerald ve Muske (2002) çalışmalarında, genellikle kırsal kesimde yaşayan çiftlerin aynı iş yerinde görev yaptığını ve çalışma ortamlarını ekonomik kazanç sağladıkları bir yerden ziyade, yaşam alanları olarak gördüklerini tespit etmiştir.…”
Section: Introductionunclassified
“…8 Verschillende studies hebben aangetoond dat visusverlies geassocieerd is met eenzaamheid. 7,[9][10][11] De prevalentie van eenzaamheid in deze studies varieert echter. Een studie onder blinde Amerikaanse veteranen (gemiddelde leeftijd 62 jaar) rapporteerde een prevalentie van 20% gemeten met de UCLA Loneliness Scale.…”
Section: Inleidingunclassified